An update on the diagnosis and treatment of dens invaginatus. (22nd May 2017) - Zhu, J; Wang, X; Fang, Y; Von den Hoff, JW; Meng, L
Abstract: Dens invaginatus is a malformation with varying anatomical features, posing challenges to treatment. Early and accurate diagnosis plays a significant role in selecting the appropriate treatment. The diagnosis of teeth with a complex root canal system including dens invaginatus has made progress with the application of three‐dimensional imaging techniques in endodontics. Advanced treatment options provide hope for teeth that could not be saved before. This review discusses diagnostic methods and treatment options for teeth with dens invaginatus, and provides guidelines for the management of dens invaginatus cases in clinic. Current as well as traditional diagnostic techniques are summarized. Treatment options including state‐of‐the‐art alternatives are presented for coronal dens invaginatus and radicular dens invaginatus.